Problem-solving therapy for depression and common mental disorders in Zimbabwe: piloting a task-shifting primary mental health care intervention in a population with a high prevalence of people living with HIV - Cowan Frances; Kajawu Lazarus; Mesu Petra; Chibanda Dixon; Araya Ricardo; Abas Melanie A (BMC, 2011)
Abstract Background There is limited evidence that interventions for depression and other common mental disorders (CMD) can be integrated sustainably into primary health care in Africa. We aimed to pilot a low-cost multi-component 'Friendship Bench Intervention' for CMD, locally adapted from problem-solving therapy and delivered by trained and supervised female lay workers to learn if was feasible and possibly effective as well as how best to implement it on a larger scale. Method We trained lay workers for 8 days in screening and monitoring CMD and in delivering the intervention. Ten lay workers screened consecutive adult attenders who either were referred or self-referred to the Friendship Bench between July and December 2007. Those scoring above the validated cut-point of the Shona Symptom Questionnaire (SSQ) for CMD were potentially eligible. Exclusions were suicide risk or very severe depression. All others were offered 6 sessions of problem-solving therapy (PST) enhanced with a component of activity scheduling. Weekly nurse-led group supervision and monthly supervision from a mental health specialist were provided. Data on SSQ scores at 6 weeks after entering the study were collected by an independent research nurse. Lay workers completed a brief evaluation on their experiences of delivering the intervention. Results Of 395 potentially eligible, 33 (8%) were excluded due to high risk. Of the 362 left, 2% (7) declined and 10% (35) were lost to follow-up leaving an 88% response rate (n = 320). Over half (n = 166, 52%) had presented with an HIV-related problem. Mean SSQ score fell from 11.3 (sd 1.4) before treatment to 6.5 (sd 2.4) after 3-6 sessions. The drop in SSQ scores was proportional to the number of sessions attended. Nine of the ten lay workers rated themselves as very able to deliver the PST intervention. Conclusion We have found preliminary evidence of a clinically meaningful improvement in CMD associated with locally adapted problem-solving therapy delivered by lay health workers through routine primary health care in an African setting. There is a need to test the effectiveness of this task-shifting mental health intervention in an appropriately powered randomised controlled trial. Trial registration ISRCTN: ISRCTN25476759